The Programme of 1871: A Modern Instance of Natural Right Argumentation - Benoit, Paul (My University, 1978)
This thesis is a commentary on a newspaper editorial published in the Journal des Trois-Rivieres on April-20, 1871 and entitled "Programme catholique: les prochaines elections". The Programme was composed by a group of French Canadian Catholic journalists who wanted to offer their compatriots practical political advice on the upcoming Quebec general election. In effect, their advice amounted to qualified support of the governing Conservative party.
The authors statement of support for the Conservative party was preceded, however, by an argument that was the basis for their advice. The major premise of the argument affirmed that politics is subordinate to religion; the minor premise, that in a country like Canada every religious community should have the necessary practical freedom to exercise its form of worship.
In making this argument, the authors of the text took a stand on the age old question of Church-State relations. According to the programmistes, the State is "negatively dependent" on the Church. That is the essential relation making for order in society. Care must be taken, therefore, to have that relation reflected in society's institutions.
Study of the Programme is enlightening at at least three different levels. Historically, the text was a controversial issue in the 1871 general election: it revealed a deep division in the Conservative party in Quebec and affected that party's subsequent development. Politically, it presented a coherent account of the structure and operation of Parliamentary Government, with special reference to the constitutional position of Quebec after Confederation. Philosophically, it was a strong argument for an "authoritarian", as opposed to a "libertarian", society: and for the traditional "natural", as opposed to the modern "naturalistic" view of the world.
The bulk of my thesis is devoted, therefore, to explicating, at one level or another, the substance of the Programme.
In my approach, I have tried to combine a classicist's respect for the text before him with a jurist's respect for the case before him. This led me, in the first place, to be careful not to impose any artificial construction on the text. Instead, I have tried to allow the text to speak for itself as much as possible, and indeed even to allow its authors to make their own comments. At the same time, I had to do justice to the text's multidimensionality, and above all to its practical and moral thrust. These considerations resulted in an approach bearing some resemblance to the "case study" method familiar to students of law and administration. This method focuses on an event, on something that presents a clearly defined and usually very limited surface ares, while often giving rise at the same time to far ranging considerations. My concern, then, with the Programme both as a text and as a case prompted me to label my approach "jurisprudential". It is an approach which I believe could usefully be taken up by other students of society.
Keywords: Religion; Religion